Semiotic Study on Cigarette Advertisements - Yudi Agus Setiawan; Norma Eralita (LPPM Universitas Buddhi Dharma, 2023)
Semiotic is study of sign. The signs deliver communicative message through verbal (gestures and utterance) or non-verbal information (body language) that leads viewers comprehend the message well. Based on the type, sign divided into three, they are icon, index and symbol. This research analyzes three types of sign, icon, index, symbol on cigarette advertisement. The data of this research are cigarette advertisements which consist of 2 different cigarette brands from two biggest cigarette companies in Indonesia Djarum and Gudang Garam. Those data are then classified into sign (icon, symbol and index). This research applied descriptive qualitative method. To classify the type of sign, the researcher used Pierce theory (Coleman, 2017). Based on the analysis on cigarettes advertisement, each advertisement contains own icon, index, symbol meaning. The icons in the cigarettes advertisement consisted of pictures of human, things and cigarettes product’s logos. While the indexes found in television cigarettes advertisement were mostly the pictures of the human attitude, things, and slogan or the cigarettes brands. From the icon, index, symbol, it can be seen the male characters as their theme. The men's characters used as the theme of cigarettes advertisement are brave, tough, masculine, fond of challenges and strong.